Deletion of acetate transporter gene ADY2 improved tolerance of Saccharomyces cerevisiae against multiple stresses and enhanced ethanol production in the presence of acetic acid. (December 2017) - Zhang, Mingming; Zhang, Keyu; Mehmood, Muhammad Aamer; Zhao, Zongbao Kent; Bai, Fengwu; Zhao, Xinqing
Graphical abstract: Highlights: Zinc sulfate supplementation repressed transcription of acetate transporter gene ADY2 . ADY2 deletion improved yeast tolerance to acetic acid and hydrogen peroxide. ADY2 deletion led to improved ethanol fermentation in the presence of acetic acid. Decreased intracellular acetic acid and ROS was revealed by ADY2 deletion. Abstract: The aim of this work was to study the effects of deleting acetate transporter gene ADY2 on growth and fermentation of Saccharomyces cerevisiae in the presence of inhibitors. Comparative transcriptome analysis revealed that three genes encoding plasma membrane carboxylic acid transporters, especially ADY2, were significantly downregulated under the zinc sulfate addition condition in the presence of acetic acid stress, and the deletion of ADY2 improved growth of S. cerevisiae under acetic acid, ethanol and hydrogen peroxide stresses. Consistently, a concomitant increase in ethanol production by 14.7% in the presence of 3.6 g/L acetic acid was observed in the ADY2 deletion mutant of S. cerevisiae BY4741. Decreased intracellular acetic acid, ROS accumulation, and plasma membrane permeability were observed in the ADY2 deletion mutant. These findings would be useful for developing robust yeast strains for efficient ethanol production.